(3fbhd ef GdLhgQIs - (3EHQGgje GddbGfj GdeGdcjs
(3ChdgG (B:s
(3hdeG PcQ Cf GdQhM JbHV hMbjbI GdbHV eSc GdTF HGdjO agh jTYQ HLSejJgG hcd LSe eYQV ddafGA hbGHd dg HGdTgGOI s
(3BNQgG (B:s
(3Ke bGd hgPG Ef UM Yf ZGjI GdLed Edi BNQ eG eQ Ke bGd hGdPjf jXgQ di hGaYdg ai GdUdGg hZjQgG GdEjJGf HdaX GdSjO EfJgGA hGddg CYde HGdUhGH fbd ef GdLhgQI hEfJgGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI HChdgGs
(3HBNQgG fbhd eNJdaIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs